2018
DOI: 10.1038/s41598-018-30691-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress decreases the redox ratio and folate content in the gut microbe, Enterococcus durans (MTCC 3031)

Abstract: Gut microbiome plays an important role in determining the effectiveness of cancer therapy. The composition of the microbiome is crucial to maintain good digestive health in the host, and to prevent and treat colorectal cancers. Most cancer therapies employ oxidative stress, which disturbs the redox status of the cell, and consequently affect growth, reductive biosynthesis and cell death. Therefore, oxidative stress can undesirably affect the gut microbiome. Hence, it is important to understand the impact of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Indeed, B9 is important for the gut immune system as it is necessary for T reg cell survival and mice fed a vitamin B9-deficient diet showed increased susceptibility to intestinal inflammation. [94,95] On the other hand, oxidative stress in the gut may lower the bacterial folate production as demonstrated in the model gut bacterium Enterococcus durans, [96] which may impact the host. However, there is some controversy for dietary folate supplementation in disease as both folate deficiency as high dose supplementation of the synthetic dietary form of FA have been associated with colon cancer.…”
Section: Vitamin B9-folatementioning
confidence: 99%
“…Indeed, B9 is important for the gut immune system as it is necessary for T reg cell survival and mice fed a vitamin B9-deficient diet showed increased susceptibility to intestinal inflammation. [94,95] On the other hand, oxidative stress in the gut may lower the bacterial folate production as demonstrated in the model gut bacterium Enterococcus durans, [96] which may impact the host. However, there is some controversy for dietary folate supplementation in disease as both folate deficiency as high dose supplementation of the synthetic dietary form of FA have been associated with colon cancer.…”
Section: Vitamin B9-folatementioning
confidence: 99%
“…It is clear, therefore, that MS is a multi-factorial pathology and genetic, environmental, and immunological factors are included in its etiology. Multiple sclerosis appears particularly in young women (female:male ratio = 3:1), especially in those women who have suffered intestinal disorders since birth (Jose et al, 2018;Sauma and Casaccia, 2020). It has been recently shown that an alteration of the intestinal microbiota leads to over-stimulation of immune cells with a higher incidence of the development of autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and MS (Brown et al, 2019).…”
Section: Autoimmunity and Multiple Sclerosismentioning
confidence: 99%
“…Lactobacillus plantarum YW11 [ 135 ], Lactobacillus plantarum CCFM10 [ 136 ], and Enterococcus durans MTCC 3031 [ 137 ] were found to restore microbial integrity in aging murine models through normalization of the redox ratio. On the other hand, gut metabolism in mice could be disrupted following administration of antibiotics, which was characterized by a shift of the redox potential after just 24 h [ 138 ].…”
Section: Is There a Relationship Between Oxidative Stress And Gut mentioning
confidence: 99%